2015
DOI: 10.1002/2015ja021143
|View full text |Cite
|
Sign up to set email alerts
|

Global MHD simulations of Mercury's magnetosphere with coupled planetary interior: Induction effect of the planetary conducting core on the global interaction

Abstract: Mercury's comparatively weak intrinsic magnetic field and its close proximity to the Sun lead to a magnetosphere that undergoes more direct space‐weathering interactions than other planets. A unique aspect of Mercury's interaction system arises from the large ratio of the scale of the planet to the scale of the magnetosphere and the presence of a large‐size core composed of highly conducting material. Consequently, there is strong feedback between the planetary interior and the magnetosphere, especially under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
168
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 96 publications
(177 citation statements)
references
References 55 publications
9
168
0
Order By: Relevance
“…These time-varying changes in electric currents and their associated magnetic fields generate induced currents at the boundaries between the conductive core and the relatively resistive mantle of Mercury to cancel out magnetic field perturbations inside the core. Outside the conductive core, however, the induced currents temporarily increase magnetic fields in Mercury's magnetosphere, from a few nano-Tesla to hundreds of nano-Tesla, depending on the solar wind dynamic pressure variations (Jia et al 2015). It has been theoretically suggested that the induced magnetic fields keep the magnetopause at ∼1.1-1.2 R M (Hood & Schubert 1979;Suess & Goldstein 1979;Jia et al 2015), and thus the solar wind would not easily access the surface of Mercury even during large dynamic pressure changes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These time-varying changes in electric currents and their associated magnetic fields generate induced currents at the boundaries between the conductive core and the relatively resistive mantle of Mercury to cancel out magnetic field perturbations inside the core. Outside the conductive core, however, the induced currents temporarily increase magnetic fields in Mercury's magnetosphere, from a few nano-Tesla to hundreds of nano-Tesla, depending on the solar wind dynamic pressure variations (Jia et al 2015). It has been theoretically suggested that the induced magnetic fields keep the magnetopause at ∼1.1-1.2 R M (Hood & Schubert 1979;Suess & Goldstein 1979;Jia et al 2015), and thus the solar wind would not easily access the surface of Mercury even during large dynamic pressure changes.…”
Section: Discussionmentioning
confidence: 99%
“…Outside the conductive core, however, the induced currents temporarily increase magnetic fields in Mercury's magnetosphere, from a few nano-Tesla to hundreds of nano-Tesla, depending on the solar wind dynamic pressure variations (Jia et al 2015). It has been theoretically suggested that the induced magnetic fields keep the magnetopause at ∼1.1-1.2 R M (Hood & Schubert 1979;Suess & Goldstein 1979;Jia et al 2015), and thus the solar wind would not easily access the surface of Mercury even during large dynamic pressure changes. Jia et al (2015), using a global MHD simulation, have studied the electromagnetic response of Mercury's interior for large solar wind dynamic pressure changes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a consequence, the magnetic field of the electric currents of the interaction is not negligible, even in the immediate proximity of the planet (e.g., Glassmeier, 2000). Furthermore, electromagnetic induction effects within the planet might be important (e.g., Grosser et al, 2004;Jia et al, 2015). To estimate the planetary magnetic field precisely, the time-dependent interaction needs to be determined.…”
Section: Introductionmentioning
confidence: 99%